Folklor Sendang Bulus Jimbung Klaten As Learning Moral Education - Sri Mulyani; Siti Muharomah; Memmy Dwi Jayanti (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this study is to describe the moral aspect and as a material for learning, while the research method used is descriptive qualitative with literature study, listen, and note down techniques. Then the data analysis technique is carried out by identifying, clarifying, analyzing, and concluding. The data source used is the folklore of Sendang Bulus Jimbung Klaten. After doing the research get the following results. There are eight sentences (8) or 62% which refer to good moral aspects and five (5) or 38% sentences refer to bad (bad) moral aspects. The thirteen (13) sentences found in the story of Sendang Bulus Jimbung will be used as learning materials in coaching the community, which are related to moral educationKeywords: folklore, moral education, and society